Contemporary spiritualities : enchanted worlds of nature, wellbeing and mystery in Italy - Palmisano, Stefania; Pannofino, Nicola (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Contemporary alternative spirituality, as studied by sociologists, is usually seen as a recent phenomenon dating from the 1960s and 1970s. However, when viewed from a longer-term perspective this form of religious expression is actually seen to reintroduce concepts that recur throughout Western cultural history. This book argues, therefore, that spirituality in the 21st Century actually shares many of the same characteristics as Classical, Mediaeval, Renaissance and Modern spiritualities. It is neither entirely new, nor is it clearly alternative to more established religions. The book is divided into two parts. The first sets out the context in which contemporary alternative spirituality has formed, charting its development as an academic term and a social phenomenon. The second part looks at how these two elements have developed in countries that are historically Catholic, focussing on specific examples in contemporary Italy: spiritualities based on the sacralisation of nature; those concerned with health and wellbeing; and those which are fascinated by mystery.Catholic majority countries are particularly interesting in this instance, as the Catholic Church has a unique cultural hegemony with which to compare alternative spiritual practices. It concludes that spirituality, if framed in a longer historical perspective, is a way of acting and seeing the world which was built, and continues to be built upon complex relations with various contradictory sources of authority, such as religion, magic thinking, secularism, rationalism, various spheres of lay culture. This is a bold take on the spirituality milieu and as such will be of great interest to scholars of Religious Studies working on the sociology of religion, contemporary spirituality and the rise of the "spiritual but not religious""--
Frenemies, spirituality and religion enchanted world of nature -- Contemporary spiritualities : a genealogy -- Contemporary spirituality in Italy -- Enchanted world of nature -- Enchanted world of wellbeing -- Enchanted world of mystery -- Key insights and future challenges.
OCLC-licensed vendor bibliographic record.
Keywords: Spirituality -- Italy; New Age movement -- Italy; Occultism -- Religious aspects -- Catholic Church; Religion and sociology -- Italy; Italy -- Religion; RELIGION / Spirituality; RELIGION / Christianity / Catholicism; RELIGION / Comparative Religion